Teachers’ Perception of the Influence of Moral Education on Pupils’ Discipline in Kericho Municipality in Kericho County; Kenya - Sang, Evaline Chebet; Prof. Isaac Njuguna. Kimengi,; Dr. Simiyu Mulambula, (IJRDO- Journal of Educational Research, 2020)
Education in Kenya aims at developing a whole round person in terms of cognitive, normative, creative and dialogical dimensions. It is believed that education can be used to change the behaviour of the learners positively. At the core of education is the triangle of discipline from without, self discipline and the sustaining force of courage from without. Teachers have served as a key element in the teaching of moral education in schools, yet research concerning teachers' perception o the influence of moral education on pupil’s discipline is limited. As a result of this scenario, the present study investigated the perception of teachers on the influence of moral education on pupils’ discipline. Reported cases of strikes, protest teenage pregnancy, burning of schools, truancy, corruption and misuse of sex are clear indicators of moral crisis in Kenya. Combinations of stratified and purposive sampling techniques were used to select the participants for the study. The target population consisted of 101 deputy head teachers and 500 teachers. The deputy head teachers were purposively sampled while the rest of the participants were randomly sampled from the various strata. The proposed study adopted Ex post facto research design. The study was based on the theory of moral development advanced by Lawrence Kohlberg. Questionnaires and interview schedule were used to collect data. From the analysis and interpretation, it was deduced that education system has failed to inculcate desired moral values to primary school pupils due to the ignorance of the role moral education play in curbing indiscipline related problems. On the basis of findings, recommendations and suggestions were found useful to curriculum developers, teacher training institutions, teachers and primary school managers in strategizing ways of improving perception of teachers towards moral education.